Linguistic and linguistic-cultural urban space (on the example of Bydgoszcz) - Święcicka, Małgorzata (Język(i) w czasie i przestrzeni, 2021)
The article deals with selected aspects of the functioning of urban space in language and culture, which was illustrated by the example of the city of Bydgoszcz. Statements presented in the article, as understood by the author, may be to a certain extent related to the linguistic and cultural space of other Polish cities in general. The article is, on the one hand, a review of existing approaches, accompanied by theoretical and methodological remarks, and on the other – a proposal of new research perspectives. The concept outlined in the article leads to the conclusion that both linguistically and linguistically-culturally captured urban space is a complex semantic (semiotic) structure, resulting from factors of various nature: history, geography, demography, cultural trends, technological achievements, etc., as well as from the type of a cultural text taken as the basis for reconstruction of meanings. Thus, the language(s) functioning within a given urban space, as well as its language images or stereotypes of its inhabitants, in comparison to any other city, on the one hand, can be characterized by the similarity of exponents representing nationwide language development trends, and on the other hand – by a number of peculiarities, including those rooted in stereotypes. The outlined research perspectives should encourage further linguistic and linguistic-cultural studies on the phenomenon of urban space, which is constantly dynamic and open.